Cadmium-induced disruption in 24-h expression of clock and redox enzyme genes in rat medial basal hypothalamus : prevention by melatonin - Jiménez Ortega, Vanesa (2011)
Fil: Jiménez Ortega, Vanesa. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España